A note on the acoustic assessment of bottlenose dolphin behaviour around fishing gears in the Asinara Island National Park, Italy - Lauriano, G.; Bruno , S. (J. Cetacean Res. Manage., 2023)
Common bottlenose dolphins co-exist with artisanal fisheries in the Asinara Island National Park area (northwestern Sardinia, Italy) and are blamed for damage to some fisheries. To investigate this, two T-POD echolocation loggers were used between July 2003 and October 2004 to monitor the occurrence and behaviour of dolphins in the proximity of three different fishing gear types. With the support of local fishermen, the T-PODs were opportunistically deployed on trammel nets set for striped red mullet or for lobster and on bottom traps set to catch benthic fish species. Inter-click Intervals (ICI) and the Pulse Repetition Frequency (PRF) have been adopted as indicators of dolphins echolocation behaviour in the proximity of fishing gears (Leeney and Tregenza, 2006). PRF values were found to be consistently higher in proximity to trammel nets for striped red mullets compared to the other gears. Moreover, ICI values in the proximity of red mullet trammel nets were found to be statistically lower than those recorded both around trammel nets for lobster (p<0.01) and around traps (p<0.01). These findings suggest that feeding related activities by dolphins could be absent or take place at very low levels in the proximity of traps and, to a lesser extent, in the proximity of trammel nets set for lobster, but may occur more regularly around nets for striped red mullet. The results show that static acoustic monitoring can detect significant differences in dolphin echolocation behaviour around different fishing gears. The findings seem to be consistent with previous evidence of interactions between bottlenose dolphins and fishing gear types in the area.